Microplastic pollution in aquatic environments: a meta-analysis of influencing factors and methodological recommendations - Hartz, Linus; Grabinski, Lisa; Salameh, Samir (Frontiers in Environmental Science, 2025)
Microplastics have become prominent environmental pollutants in both marine and freshwater systems, which raises ecological and health concerns. This study provides a comprehensive meta-analysis of microplastic concentration data from over 60 studies across Europe, investigating factors influencing microplastic distribution. The investigated influences include sampling latitude, proximity to wastewater treatment plants, population density in the sampling area, sampling mesh size, distance to coastlines, seasonal variations, and wind speeds. The results indicate that microplastic concentrations correlate with mesh size in marine but not freshwater environments, suggesting the predominant microplastic type in fresh waters to be primary microplastics. Although it is generally accepted, that waste water treatment plants contribute to microplastic pollution, this study identifies other more significant factors, such as surface runoff and atmospheric deposition. Population density shows a modest influence, while the distance of sampling site from coastlines is, contrary to findings from other publications, not significantly related to microplastic concentration levels. Seasonal and wind speed effects are complex, with varied impacts across sampling locations and used correction factors have to be critically reevaluated. This analysis underscores the need for standardized methodologies in microplastic research, and it recommends specific sampling practices to enhance data comparability across studies, which contributes to a more accurate assessment of microplastic pollution in aquatic environments.